OPTIMALISASI PEMBELAJARAN IPA MELALUI PENGUATAN LITERASI DIGITAL SISWA SEKOLAH DASAR - Trivena; Susanna Vonny Noviana Rante (STKIP Subang, 2026)
The rapid advancement of digital technology has increased elementary school students' access to gadgets. However, their use remains predominantly focused on non-educational activities, limiting their potential contribution to the learning process. This condition was also identified at UPT SDN 2 Kurra, Tana Toraja Regency, where students had not yet utilized gadgets effectively to support science learning. This community service program aimed to optimize science learning by strengthening students' digital literacy through education on the responsible use of gadgets. The program was conducted on June 11, 2026, using a Participatory Action Approach (PAA) involving 42 fourth- and fifth-grade students and 13 teachers. The activities consisted of digital wellbeing education for students through the implementation of the 20-20-20 rule and the